Implosion : ett postmodernt perspektiv - Nittve, Lars; Celant, Germano; Linker, Kate; Owens, Craig (Stockholm : Moderna museet, 1987)
Bender, Gretchen ; Birnbaum, Dara ; Broodthaers, Marcel ; Buren, Daniel ; Duchamp, Marcel ; Johns, Jasper ; Judd, Donald ; Kosuth, Joseph ; Kruger, Barbara ; Lawler, Louise ; Levine, Sherrie ; Longo, Robert ; Mc Collum, Allan ; Merz, Gerhard ; Morris, Robert ; Mucha, Reinhard ; Paik, Nam June ; Palermo, Blinky ; Paolini, Giulio ; Picabia, Francis ; Polke, Sigmar ; Rauschenberg, Robert ; Richard, Gerhard ; Rosenquist, James ; Sherman, Cindy ; Simmons, Laurie ; Warhol, Andy ; Welling, James
Implosion : ett postmodernt perspektiv / a postmodern perspective, Moderna Museet, Stockholm, 24.10.1987 - 10.01.1988
kunstcatalogus